LIQUIDITY, LEVERAGE, AND COMPANY SIZE AS PREDICTORS OF PROFITABILITY IN LQ-45 NON-FINANCIAL COMPANIES ON IDX INDONESIA - Nasywa Fauziyyah; Dani Sopian (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to examine the influence of liquidity, leverage, and company size as predictors of profitability in non-financial companies listed in the LQ-45 Index on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The research population amounted to 45 companies, and through purposive sampling techniques, 17 companies were obtained with a total of 85 observation units. Independent variables used include liquidity proxied by Current Ratio (CR), leverage proxied by Debt to Asset Ratio (DAR), and company size measured using the natural logarithm of total assets. Profitability as a dependent variable is measured using Return on Asset (ROA). The analysis method used was multiple linear regression with the help of SPSS 27 software. The results of the study partially show that liquidity does not have a significant effect on profitability, leverage does not have a significant effect on profitability, while company size has a negative and significant effect on profitability. Simultaneously, liquidity, leverage, and company size had a significant effect on profitability with an F value of 6.564 and an R Square value of 0.198. These findings suggest that in large-scale companies in the LQ-45 Index, an increase in asset scale is not always directly proportional to an increase in profitability.